The potential impact of RV144-like vaccines in rural South Africa: a study using the STDSIM microsimulation model - Hontelez, Jan; Bärnighausen, Till; Tanser, Frank; Newell, Marie-Louise; Baltussen, Rob M. P. M. (Vaccine, 2011)
The only successful HIV vaccine trial to date is the RV144 trial of the ALVAC/AIDSVAX vaccine in Thailand, which showed an overall incidence reduction of 31%. Most cases were prevented in the first year, suggesting a rapidly waning efficacy. Here, we predict the population level impact and cost-effectiveness of practical implementation of such a vaccine in a setting of a generalised epidemic with high HIV prevalence and incidence. We used STDSIM, an established individual-based microsimulation model, tailored to a rural South African area with a well-functioning HIV treatment and care programme. We estimated the impact of a single round of mass vaccination for everybody aged 15-49, as well as 5-year and 2-year re-vaccination strategies for young adults (aged 15-29). We calculated proportion of new infections prevented, cost-effectiveness indicators, and budget impact estimates of combined ART and vaccination programmes. A single round of mass vaccination with a RV144-like vaccine will have a limited impact, preventing only 9% or 5% of new infections after 10 years at 60% and 30% coverage levels, respectively. Revaccination strategies are highly cost-effective if vaccine prices can be kept below 150 US$/vaccine for 2-year revaccination strategies, and below 200 US$/vaccine for 5-year revaccination strategies. Net cost-savings through reduced need for HIV treatment and care occur when vaccine prices are kept below 75 US$/vaccine. These results are sensitive to alternative assumptions on the underlying sexual network, background prevention interventions, and individual's propensity and consistency to participate in the vaccination campaign. A modestly effective vaccine can be a cost-effective intervention in highly endemic settings. To predict the impact of vaccination strategies in other endemic situations, sufficient knowledge of the underlying sexual network, prevention and treatment interventions, and individual propensity and consistency to participate, is key. These issues are all best addressed in an individual-based microsimulation model.